2020
DOI: 10.1126/scitranslmed.aay7856
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Beclin1 promotes direct cardiac reprogramming

Abstract: Direct reprogramming of fibroblasts to alternative cell fates by forced expression of transcription factors offers a platform to explore fundamental molecular events governing cell fate identity. The discovery and study of induced cardiomyocytes (iCMs) not only provides alternative therapeutic strategies for heart disease but also sheds lights on basic biology underlying CM fate determination. The iCM field has primarily focused on early transcriptome and epigenome repatterning, whereas little is known about h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…6F), including the Kat family and Esco family. In addition, the promoter region of another acetylation transferase-Lef1 (distance to TSS: − 82) shows significant changes and upregulation in RNA expression; this supports the evidence that Lef1 is a regulator for cardiac reprogramming and cardiac hypertrophy (Lai et al, 2019;Wang et al, 2020) (Fig. 6E).…”
Section: New Epigenetic Targets Discovery and Validationsupporting
confidence: 80%
“…6F), including the Kat family and Esco family. In addition, the promoter region of another acetylation transferase-Lef1 (distance to TSS: − 82) shows significant changes and upregulation in RNA expression; this supports the evidence that Lef1 is a regulator for cardiac reprogramming and cardiac hypertrophy (Lai et al, 2019;Wang et al, 2020) (Fig. 6E).…”
Section: New Epigenetic Targets Discovery and Validationsupporting
confidence: 80%
“…Moreover, AKT1 overexpression was not associated with altered proliferation or apoptosis [107]. The role of mTORC1, however, is still controversial as Wang et al observed enhanced reprogramming efficiency following rapamycin treatment, which they attributed to increased autophagy due to mTORC1 inhibition [109], in contrast to the impaired reprogramming observed by Zhou et al upon mTORC1 inhibition [107].…”
Section: Strategies For In Vitro Direct Cardiac Reprogrammingmentioning
confidence: 98%
“…Autophagic factor Becn1 suppressed iCMs induction in an autophagy-independent manner, meanwhile depletion of Becn1 resulted in improved iCMs induction from both murine and human fibroblasts. [169] Moreover, the induction effects from Becn1 knockdown is independent of autophagy induction due to activation of the canonical Wnt/β-catenin pathway. [169] In addition, direct in vivo reprogramming have led to the generation of functionally maturer iCMs than those obtained in vitro condition.…”
Section: Reprogramming-based Regenerative Therapymentioning
confidence: 99%
“…[169] Moreover, the induction effects from Becn1 knockdown is independent of autophagy induction due to activation of the canonical Wnt/β-catenin pathway. [169] In addition, direct in vivo reprogramming have led to the generation of functionally maturer iCMs than those obtained in vitro condition. [170][171][172] Therefore, it is suggested that local environment plays significant role in the efficacy of fibroblast direct reprogramming.…”
Section: Reprogramming-based Regenerative Therapymentioning
confidence: 99%